Polymeric Patches Based on Chitosan/Green Clay Composites and Hazelnut Shell Extract as Bio-Sustainable Medication for Wounds - Carmen Laura Pérez Gutíerrez; Alessandro Di Michele; Cinzia Pagano; Debora Puglia; Francesca Luzi; Tommaso Beccari; Maria Rachele Ceccarini; Sara Primavilla; Andrea Valiani; Camilla Vicino; Maurizio Ricci; César Antonio Viseras Iborra; et al. (MDPI AG, 2023)
Hazelnut shells, the main waste deriving from hazelnut processing, represent an interesting source of active molecules useful in pharmaceutics, although they have not yet been examined in depth. A hydrosoluble extract (hazelnut shell extract, HSE) was prepared by the maceration method using a hydroalcoholic solution and used as the active ingredient of patches (prepared by casting method) consisting of composites of highly deacetylated chitosan and green clay. In vitro studies showed that the formulation containing HSE is able to stimulate keratinocyte growth, which is useful for healing purposes, and to inhibit the growth of S. aureus (Log CFU/mL 0.95 vs. 8.85 of the control after 48 h); this bacterium is often responsible for wound infections and is difficult to treat by conventional antibiotics due to its antibiotic resistance. The produced patches showed suitable tensile properties that are necessary to withstand mechanical stress during both the removal from the packaging and application. The obtained results suggest that the developed patch could be a suitable product to treat wounds.